Field research contextualizes local risk behaviors in northern Vietnam - Higgs, Peter (Mary Ann Liebert, Inc., 2015)
The estimated number of drug users across Vietnam varies between 128,000 and 183,000 depending on sources of data which are used. However, the actual number of users is unknown and believed to be higher than these estimates, since the beginning of 2002 many have been arrested and sent to mandatory ‘rehabilitation centers’. Despite increases in spending HIV remains a massive problem among people who inject drugs. This image and the attached field note are striking in their ability to tell a story about poverty and inadequate treatment for opiate use in Vietnam.